تصريف الأسماء - تدريبات تطبيقية = Tasrif al-asma' tadribat tatbiqiyyah - Ismail, Yasir; Sahrir, Muhammad Sabri (IIUM Press, International Islamic University Malaysia, 2017)
The Arabic language sub-science known as صرف – is referring roughly to what we know as Morphology - is a subject through which one learns the internal assembly of a word by way of patterns of vowelization and introduction of extra letters—or what we call a template. This book presents the study of Arabic Morphology in terms of nouns from various topics such as Dual and Plural (al-’Ifrād wa at-Tathniyyah wa al-Jam’), the various Plural forms, including both the Masculine and the Feminine Plural (Jam’ai as-Salāmah) and the rules governing them, the Broken Plurals (Jam’ at-Taksīr) both of Paucity (al-Qillah) and Multitude (al-Kathrah), and the conditions for their formation, the Diminutive (at-Tasghīr), the Relative Nouns (an-Nasab), and the rules which govern them, as well as presenting students with the concept of Transformation and Assimilation of letters within nouns and verbs (al-’I’lāl wa al-’Ibdāl), and their resulting morphological changes. Every morphological topic in this book is enhanced with practical examples, exercises, extra reference for further reading and answer schemes for all morphological exercises at the last part of this book as well as word indexes. In addition, all Arabic words in this book are provided with diacritic symbols (tasykeel) that are crucial to non-native Arabic learners to read and identify how words are pronounced and to disambiguate their meanings. This book is suitable to be used by learners at various universities and schools within the similar syllabus.